POLEMIK Ã¢â‚¬Å“AHLI BIDÃ¢â‚¬â„¢AHÃ¢â‚¬Â DALAM WACANA ULÃ…ÂªMUL HADÃ„ÂªÃ¡Â¹Â : Evaluasi Ibnu Ã¡Â¸Â¤ajar al-Ã¢â‚¬ËœAsqalÃ„Âny Terhadap Status RiwÃ„Âyat al-MubtadiÃ¢â‚¬â„¢ - dan Ismangil Ngarfillah, Asep Nahrul Musadad (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2016)
AbstractOne of the key terms employed in showing the connection between jarh wa taÃ¢â‚¬â„¢dÃ„Â«l discourse and Islamic sectarianism issues is bidÃ¢â‚¬â„¢ah Ã¢â‚¬Å“heresyÃ¢â‚¬Â and al-mubtadiÃ¢â‚¬â„¢ Ã¢â‚¬Å“heretic transmitterÃ¢â‚¬Â. Start on preliminary introduction to bidÃ¢â‚¬â„¢ah conception in the context of jarÃ¡Â¸Â¥ wa taÃ¢â‚¬â„¢dÃ„Â«l, this article discusses Ibn Ã¡Â¸Â¤ajar al-Ã¢â‚¬ËœAsqalÃ„ÂniÃ¢â‚¬â„¢s notions about the concept of heresy (bidÃ¢â‚¬â„¢ah) and validity of heretic transmitter (riwÃ„Âyat al-mubtadiÃ¢â‚¬â„¢). IbÃ¡Â¹â€¡ Hajar was choosed here as the exponent of culmination in Ã¢â‚¬Å“ulÃ…Â«m al-hadÃ„Â«tÃ¡Â¸Â£Ã¢â‚¬Â discourse in which the bidÃ¢â‚¬â„¢ah notion was arguably reconsidered along with the still-functioning Islamic sectarianism polemic. It deals finally with Ã¢â‚¬Å“kafirÃ¢â‚¬Â claims (takfÃ„Â«r) as the so-called Ã¢â‚¬Å“theological weaponÃ¢â‚¬Â to blame others.Keywords; Ibnu Hajar al-Ã¢â‚¬ËœAsqalÃ„Âni, bidÃ¢â‚¬â„¢ah, dan riwÃ„Âyat al-mubtadiÃ¢â‚¬â„¢